Nickel Allergy of the Skin and Beyond - Gergovska, Malena; Darlenski, Razvigor; Kazandjieva, Jana (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Hypersensitization to nickel is one of the most common contact allergies in the modern world and it is considered to be a major cause of contact dermatitis, especially for hand eczema. Objective: The aim of this paper is to describe many faces of the nickel allergy and to find out different diagnostic, potential strategies for treatment and prevention in hypersensitized patients. A personal clinical experience with practical clinical cases of contact dermatitis to nickel has also been presented. Methods: Electronic databases on this topic was carried out using PubMed-Medline. Results: The literature review identified many articles reporting for nickel contact allergy and pointing the metal as number one allergen in the frequency of positive skin patch test reactions in a large population worldwide. Herein, a summary of the current understanding and evidence on nickel allergy with practical approach and proposed recommendations to the dermatologist, general practitioner, and the allergist were prepared. Conclusion: The prevalence of nickel allergy represents an important socio-economical and health issue. Metal is one of the most common sensitizing agents worldwide. The morbidity due to this metal represents the allergic contact dermatitis and it is constantly growing in many countries. There are also cases of systemic allergic contact dermatitis, where they could be easily misdiagnosed as adverse drug reactions, which lead to delay of the correct diagnosis and inappropriate treatment.
Keywords: specific nickel-scavenging agents